2015
DOI: 10.1088/1742-5468/2015/11/p11021
|View full text |Cite
|
Sign up to set email alerts
|

Counterpart synchronization of duplex networks with delayed nodes and noise perturbation

Abstract: Abstract. In the real world, many complex systems are represented not by single networks but rather by sets of interdependent ones. In these specific networks, nodes in one network mutually interact with nodes in other networks. This paper focuses on a simple representative case of two-layer networks (the so-called duplex networks) with unidirectional inter-layer couplings. That is, each node in one network depends on a counterpart in the other network. Accordingly, the former network is called the response la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In 2014, Aguirre et al revealed that the connector nodes between layers play an important role in the synchronizability of interconnected networks [19]. Further, intra-layer synchronization, inter-layer synchronization, counterpart synchronization, and generalized synchronization in multiplex networks have been investigated [20][21][22][23][24]. Tang et al proposed three necessary regions to describe the different types of coherent behaviors (such as complete synchronization, intra-layer synchronization, and inter-layer synchronization) in multiplex networks based on the master stability function method [25].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Aguirre et al revealed that the connector nodes between layers play an important role in the synchronizability of interconnected networks [19]. Further, intra-layer synchronization, inter-layer synchronization, counterpart synchronization, and generalized synchronization in multiplex networks have been investigated [20][21][22][23][24]. Tang et al proposed three necessary regions to describe the different types of coherent behaviors (such as complete synchronization, intra-layer synchronization, and inter-layer synchronization) in multiplex networks based on the master stability function method [25].…”
Section: Introductionmentioning
confidence: 99%
“…At present, many scholars have explored the synchronization of complex networks [16][17][18]. Due to the disturbances of networks, there have been many works in the field of synchronization for complex networks with stochastic disturbances [19][20][21][22][23][24][25]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [24], the synchronization between each node in the drive layer and its counterpart in the response layer of this sort of duplex networks with delayed nodes and noise perturbation is explored. Though there is increasing research relating to the synchronization of interdependent networks [8,9,26], few people have explored the synchronization problem of interdependent networks with stochastic disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Interlayer synchronization is also called counterpart synchronization [11] which describes how the nodes in one network behave coherently with the corresponding ones in other connected networks. This concept can be regarded as the development of synchronization for coupled driveresponse systems [12].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of interlayer synchronization can be also understood as outer synchronization [13] between two coupled networks. In the past decade, it has gained considerable attention-see [11,[13][14][15][16][17][18][19][20] and the references therein. Some control schemes have been proposed to realize all kinds of outer synchronization such as complete outer synchronization [13][14][15][16][17], inverse outer synchronization [18], generalized outer synchronization [19], and finite-time outer synchronization [21].…”
Section: Introductionmentioning
confidence: 99%